SHARQ MUTAFAKKIRLARI VA MA’RIFATPARVAR ALLOMALARIMIZNING TA’LIM RIVOJIGA QO‘SHGAN HISSALARI - Nabiyeva Dilfuza Temirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, by considering the thoughts of our great enlightened ancestors who contributed to our present day education system, who laid the foundation stone, the future primary school o to develop the spirituality of teachers.